Penerapan Sanitasi di PT. CentralPertiwi Bahari (Fish Feed Mill) Tanjung Bintang Lampung Selatan - Alika Tatia Amarta; Natalina Natalina (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Sanitation is an important aspect in the fish feed industry to ensure product quality, product safety, and employee health. PT. CentralPertiwi Bahari is a fish feed industry that has implemented sanitation as part of its product quality assurance system. This study aims to examine the implementation of sanitation at PT. CentralPertiwi Bahari to obtain an overview of the implementation of sanitation based on Permenkes No. 70 of 2016. This study uses a qualitative descriptive method carried out in January-February 2025. Data collection was carried out through observation, interviews, document reviews and scientific literature. Aspects studied include external environmental sanitation, factory environmental sanitation, building sanitation, production process sanitation, raw material sanitation, and employee sanitation. The results of the study indicate that PT. CentralPertiwi Bahari has implemented sanitation in accordance with the provisions of Permenkes No. 70 of 2016 as indicated by clean environmental and building conditions, the availability of good sanitation facilities, proper management of raw materials, and employee sanitation that is consistently implemented. The implementation of sanitation at PT. CentralPertiwi Bahari has supported efforts to maintain quality and occupational health. However, conditions requiring attention, such as water pooling outside the factory during rainy seasons, require remedial measures to optimize sanitation implementation. The results of this study are expected to serve as a basis for company evaluation and a reference for similar industries in improving sustainable sanitation practices.